2021
DOI: 10.1177/10996362211063152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and thermal cycles on the mechanical properties of expanded polystyrene foam

Abstract: Understanding the effects of high temperature and thermal cycles on the mechanical properties of expanded polystyrene (EPS) foam is critical for its use in sandwich panels. This paper presents an experimental investigation of these effects in typical environmental conditions that exist in construction applications. A total of 117 small specimens were cut from metal-faced sandwich panels with EPS core and were exposed to different numbers of thermal cycles and/or sustained high temperatures. The specimens were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Expanded polystyrene (EPS), a white color foam primarily used for packaging and insulation, is basically produced from small spherical solid beads of polystyrene (Rydzkowski et al, 2020). It is a lighter material and exhibits excellent adaptability, greater dimensional stability, high resistance toward bending and compression, less toxicity, high moisture resistance, and remarkable thermal insulation properties (Ramli Sulong et al, 2019; Tahir & Hamed, 2022; Wasiu & Baba, 2020). Hence, these properties make it an excellent material for packaging and construction (buildings, roads, railway, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Expanded polystyrene (EPS), a white color foam primarily used for packaging and insulation, is basically produced from small spherical solid beads of polystyrene (Rydzkowski et al, 2020). It is a lighter material and exhibits excellent adaptability, greater dimensional stability, high resistance toward bending and compression, less toxicity, high moisture resistance, and remarkable thermal insulation properties (Ramli Sulong et al, 2019; Tahir & Hamed, 2022; Wasiu & Baba, 2020). Hence, these properties make it an excellent material for packaging and construction (buildings, roads, railway, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This study provides continuity for recent work reported in the literature about the mechanical behavior of foams under high temperature conditions. [12][13][14] Experimental methodology…”
Section: Introductionmentioning
confidence: 99%